(untitled) (Psicologia USP, 2014)
Domestic violence damages the mental health of women and is associated with low self-esteem and depression. In promoting actions to deal with this injury, there is the work of psychologists. This study aimed to understand the meaning of psychological support to women in situations of domestic violence within the Family Health Strategy. It was held interviews with 52 professionals working in health units in Santa Catatina, Brazil. The collection and analysis of data were based on Grounded Theory. Health professionals mean that women experience of domestic violence need psychological support and refer to the psychologist, considering them better prepared for the empowerment of women in order to break with the violence. However, complain about the limited number of psychologists, considering the demand in the community. Signals to the need to rethink health actions in the context of Primary Health Care, from the integration and intersectoral processes so that women needed psychological support for coping with domestic violence is ensured.